Dentists' and dental students' attitudes, knowledge, preparedness, and willingness related to treatment of people living with HIV/AIDS in China. (18th July 2016) - Lee, Cliff; Fan, Yuehong; Starr, Jacqueline R.; Dogon, I. Leon
Abstract: Objectives: This study aims to assess the attitudes, knowledge, preparedness, and willingness of dentists and dental students to treat people‐living‐with‐HIV/AIDS (PLWHA) in China, and to determine the factors associated with willingness to treat. Methods: We surveyed dentists and dental students in hospitals and dental schools in five regions in China with varying PLWHA prevalence. Survey questions covered demographics, as well as four categories regarding treating PLWHA: knowledge (scaled 0–1), attitude (scaled 1–4), preparedness (scaled 1–4), and willingness to treat (scaled 1–4). Composite scores for each category were calculated as weighted means. Confounder‐adjusted regression analysis was performed to determine the factor(s) correlated with willingness to treat. Results: We collected 394 (84 percent) and 462 (90 percent) useable surveys from dentists and dental students respectively. Dentists' mean composite scores were 0.63 (poor knowledge), 2.1 (negative attitude), 2.8 (adequate preparedness), and 2.5 (neutral willingness). Students' mean composite scores were 0.64 (poor knowledge), 2.3 (negative attitude), 2.7 (adequate preparedness), and 2.6 (positive willingness). Forty‐five percent of dentists and 59 percent of dental students had scores indicating positive willingness to treat. Attitude was the only factor consistently correlated with willingness to treat. Dentists and dental students scored low in all categories except for preparedness. Conclusion: It is imperative that knowledge of HIV/AIDS and attitudes toward PLWHA be further improved during dental training to increase the access to and effectiveness of dental care of PLWHA in China and to enhance their quality of life.